The great Chinese art transfer : how so much of China's art came to America - St. Clair, Michael, 1940- (Fairleigh Dickinson University Press ; The Rowman & Littlefield Publishing Group, Inc., 2016)
This is the story of one of the great outflows of art in history, that is, from China into the collections and museums of the West. Western collectors and international dealers gathered paintings, ceramics, and other art objects during a short period from 1860 into the early years of the twentieth century, and now there is a reverse flow as wealthy Chinese collectors purchase back some of these treasures.